On orbit performance of the solar flare trigger for the Hinode EUV imaging spectrometer - Brooks, David H.; Reep, Jeffrey W.; Ugarte-Urra, Ignacio; Warren, Harry P. (Frontiers in Astronomy and Space Sciences, 2023)
We assess the on-orbit performance of the flare event trigger for the Hinode EUV Imaging Spectrometer. Our goal is to understand the time-delay between the occurrence of a flare, as defined by a prompt rise in soft X-ray emission, and the initiation of the response observing study. Wide (266") slit patrol images in the He II 256.32A spectral line are used for flare hunting, and a reponse is triggered when a pre-defined intensity threshold is reached. We use a sample of 13 > M-class flares that succesfully triggered a response, and compare the timings with soft X-ray data from GOES, and hard X-ray data from RHESSI and Fermi. Excluding complex events that are difficult to interpret, the mean on orbit response time for our sample is 2 min 10 s. These results may be useful for planning autonomous operations for future missions, and give some guidance as to how improvements could be made to capture the important impulsive phase of flares.